The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1051/0004-6361/201936912
|View full text |Cite
|
Sign up to set email alerts
|

Star formation in outer rings of S0 galaxies

Abstract: Aims. Although S0 galaxies are often thought to be “red and dead”, they frequently demonstrate star formation organised in ring structures. We try to clarify the nature of this phenomenon and its difference from star formation in spiral galaxies. Here we study the moderate-luminosity nearby S0 galaxy, NGC 4513. Methods. By applying long-slit spectroscopy along the major axis of NGC 4513, we measured gas and star kinematics, Lick indices for the main body of the galaxy, and strong emission-line flux ratios in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…In addition, we only show those spaxels with high signal to noise ratio (S/N of [O i] 3), corresponding to ∼ 5 kpc from the nucleus. We see that the overall velocity distribution and dispersion of these NELs are in line with typical galactic disks (Rix et al 1992;Proshina et al 2020). We find that the velocity profiles measured from different NELs are consistent, and thus use the median of the measurement results from these different NELs, following the method employed by Courteau (1997), Weiner et al (2006) and Drew et al (2018).…”
Section: The Rotating Disksupporting
confidence: 54%
“…In addition, we only show those spaxels with high signal to noise ratio (S/N of [O i] 3), corresponding to ∼ 5 kpc from the nucleus. We see that the overall velocity distribution and dispersion of these NELs are in line with typical galactic disks (Rix et al 1992;Proshina et al 2020). We find that the velocity profiles measured from different NELs are consistent, and thus use the median of the measurement results from these different NELs, following the method employed by Courteau (1997), Weiner et al (2006) and Drew et al (2018).…”
Section: The Rotating Disksupporting
confidence: 54%
“…The CCD E2V CCD42-90, with a format of 2048 × 4600, using in the 1 × 2 binning mode provided a spatial scale of 0.357 /px and a spectral sampling of 0.86 Å/px. The data reduction as well as kinematics and stellar population characteristics derivation were standard for our SCORPIO-2 data; see for example Sil'chenko et al (2019) or Proshina et al (2020). We used the gr-band images from the SDSS/DR9 archive (Ahn et al 2012) to study the large-scale structure of the galaxy.…”
Section: Observations and The Data Involvedmentioning
confidence: 99%
“…The distance to the galaxy is 108 Mpc and the linear scale is about 0.5 kpc per arcsec (NED). This paper is a part of our series about the origin of star-forming rings in S0 galaxies; earlier NGC 6534 and MCG 11-22-015 are described by Sil'chenko et al (2018) and NGC 4513 is described by Proshina et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, this claim has been challenged and evaluated in multiple studies of S0 galaxies (see e.g. recent studies by Kostiuk & Sil'chenko 2015;Sil'chenko et al 2018;Proshina et al 2019;Sil'chenko et al 2019;Proshina et al 2020). In recent study, for example, Proshina et al (2020) considered the ring S0 galaxy NGC 4513.…”
Section: Accretionmentioning
confidence: 99%
“…According to kinematic studies of nearby lenticular galaxies, misalignments between their stellar discs and gaseous components (from 40% to 60% of early-type galaxies have cool and ionized gas, Welch & Sage 2003;Sage & Welch 2006;Welch et al 2010;Davis et al 2011;Serra et al 2012) are frequent (see e.g. Bertola et al 1992;Kuijken et al 1996;Sil'chenko & Moiseev 2006;Sil'chenko et al 2009;Katkov et al 2011;Davis et al 2011;Katkov et al 2013Katkov et al , 2015Proshina et al 2020). Davis et al (2011) showed that misaligned gaseous subsystems are four times more frequent in field lenticular galaxies than in those residing in a cluster.…”
mentioning
confidence: 99%